1995
DOI: 10.1161/01.hyp.26.4.642
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Target Organs of Hypertension

Abstract: Apoptosis or programmed cell death frequently parallels abnormalities in cell proliferation and differentiation. As hypertrophy/hyperplasia or remodeling occurs in organs affected by hypertension, we evaluated the degree of apoptosis in the heart, kidney, and brain in situ in genetically hypertensive mice and rats as well as in cultured vascular smooth muscle cells. Apoptosis was characterized by morphological features, DNA fragmentation, and laddering as well as by terminal deoxynucleotidyl transferase labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
4
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(128 citation statements)
references
References 51 publications
7
112
4
5
Order By: Relevance
“…The contribution of apoptosis to cell death of myocytes in cardiovascular disorders such as hypertension, 17 heart failure 18 and myocytic hypoxia, 6 has recently been investigated in animal models. In a study in rats, Cheng et al showed that overstretching of a single myocyte might be related to the expression of Fas and to programmed cell death, suggesting that apoptosis may cause dilatation of the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of apoptosis to cell death of myocytes in cardiovascular disorders such as hypertension, 17 heart failure 18 and myocytic hypoxia, 6 has recently been investigated in animal models. In a study in rats, Cheng et al showed that overstretching of a single myocyte might be related to the expression of Fas and to programmed cell death, suggesting that apoptosis may cause dilatation of the chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Kinin+Hoe140 had no effects on the LPS-induced increase in caspase 3 activity. npg the heart, kidney and aorta of hypertensive patients, resulting in heart failure, renal dysfunction and vascular remodeling [11] . The present study demonstrated that a single intravenous injection of rAAV-HK could protect against apoptosis in these organs of SHRs.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve three-month-old male SHRs weighing 250-280 g were randomly divided into two groups (six rats in each group). A single injection of rAAV-HK (about 1×10 11 transducing units in 1 mL of saline solution) into the tail of the SHRs was administered in the treatment group. For the control group, the SHRs were injected with rAAV-lacZ.…”
Section: Animal Treatment and Gene Deliverymentioning
confidence: 99%
“…También se ha visto que constantemente ocurre apoptosis miocárdica en órganos diana de ratas hipertensas (124).…”
Section: La Apoptosis En El Sistema Cardiovascularunclassified